Poetics of Slogans in Yachting ADS - Skračić, Tomislav; Borak, Marko (European Journal of Multidisciplinary Studies, 2016)
The paper discusses the poetics of yachting slogans – short, simple and memorable advertising statements whose task is to attract the attention of potential consumers and help differentiate the product or the company. The stylistic analysis, including qualitative, descriptive and comparative methods, has been used to identify and examine the poetic elements of slogans in yachting ads: schemes, tropes and additional imagery, with due attention paid to the graphic aspect and the comparative features of slogans in other trades. The paper primarily addresses the students and teachers of English language for Specific Purposes. The results of the analysis are useful for familiarizing with the main principles of figurative language and writing advertising texts, and can provide useful information for literature students, admen, copywriters and all people interested in language of advertising
Keywords: yachting, advertising, slogans, poetics